Exposure to external country specific shocks and income volatility - Jansen, Marion ([WTO] [Geneva]CH, 2009)
Analyzes the relevance of country specific shocks for income volatility in open economies. Shows that exposure to country specific shocks has a positive and significant impact on GDP volatility. Shows also that geographical diversification is a significant determinant of countries exposure to country specific shocks.